RIBA DALAM PINJAMAN ONLINE: TINJAUAN HUKUM ISLAM DAN REGULASI DI ERA KONTEMPORER - Rahman Pangerang; Achmad Abubakar; Sohrah Sohrah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The development of the times has brought significant changes to human lifestyles and needs, particularly through the influence of social media, which shapes individuals’ lifestyles and self-perceptions. Intensive social media interaction encourages individuals to present an idealized image to gain social recognition, often one that does not reflect their actual conditions. To fulfill these needs, many people resort to online loans. This phenomenon has implications for consumptive behavior and the pursuit of social status, which, in some cases, may encourage economic practices that are not in accordance with Islamic principles, such as riba (usury). From an Islamic perspective, riba is strictly prohibited as stated in the Qur’an and Hadith because it contradicts the values of justice and economic balance. The Indonesian Ulema Council (MUI) defines riba as an additional charge without compensation arising from deferred payment that harms one of the parties involved. Although the prohibition of riba has a strong foundation, its implementation in the modern era faces various challenges, including the dominance of interest-based economic systems, low Islamic financial literacy, and limited regulations. The purpose of this study is to analyze society's consumptive behavior in using online loans to gain social recognition through the perspectives of the Qur’an, Hadith, and MUI Fatwas. This research employs a Systematic Literature Review (SLR) to examine theories, concepts, and findings from previous studies, drawn from books, journals, and empirical approaches grounded in direct experience and observation. The findings of this study reaffirm that the concept of riba in online loans in the contemporary era creates injustice and economic imbalance in society by imposing additional charges that disadvantage one of the parties involved.